REVITALIZATION MARINA BEACH THROUGH THEMATIC FOOD COURT AND MODERN TROPICAL LIBRARY FOR SOCIO-ECONOMIC SUSTAINABILITY - Gladies Imanda Utami Rangkuty; Frendy Juniesdy Wijaya; Lathif Ade Saputra; Nicolas Lioe; Rakit Ricardo Rosario (Program Sarjana Arsitektur Universitas Internasional Batam, 2026)
The revitalization of public spaces in coastal areas is essential for improving community quality of life, particularly in Marina Beach. This study explores the potential of a thematic food court as a strategy to support socioeconomic sustainability through placemaking. Data shows a sharp decline in public visits during the COVID-19 pandemic (2020–2021), however there has been gradual recovery post-2022, with the significant increase of 8.23% in 2023, though still limited. By combining the concepts of placemaking and a community-based economy, the integration of a thematic foodcourt and a modern tropical library is expected to foster social interaction, support local MSMEs, provide free educational access (from library itself), and boost Marina Beach's tourism appeal. This qualitative, exploratory study uses field observations, stakeholder interviews, and document analysis. Findings indicate that a thematic food court can integrate local culture, stimulate the coastal economy through MSMEs, and reinforce the area's identity as a sustainable tourism destination. The inclusion of a library further enhances educational opportunities and land use value. The study recommends collaborative efforts between local community and private sectors to implement this concept as a holistic approach to coastal public space revitalization.